Recommendations Russian Society of Dermatovenerologists and Cosmetologists for systemic treatment of psoriasis during the pandemic COVID-19 - Alexey A. Kubanov; Andrey L. Bakulev; Muza M. Kokhan; Olga Yu. Olisova; ALexey V. Samtsov; Evgeny V. Sokolovskiy; Vladislav R. Khairutdinov; Marianna M. Khobeish (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
Below you will find the analysis of the first published data and international clinical recommendations for the systemic treatment of patients with moderate and severe psoriasis in the context of the COVID-19 pandemic in different countries (France, Italy, USA, Spain, and Germany).